Aeroelastic Behavior of a Wind Turbine Blade by a Fluid -Structure Interaction Analysis - Tawfik, Mauwafak A.; Abu-Tabikh, Mohammed I.; Hamdoon, Farouk O. (Al-Khwarizmi Engineering Journal, 2013)
In this paper, a numerical model for fluid-structure interaction (FSI) analysis is developed for investigating the aeroelastic response of a single wind turbine blade. The Blade Element Momentum (BEM) theory was adopted to calculate the aerodynamic forces considering the effects of wind shear and tower shadow. The wind turbine blade was modeled as a rotating cantilever beam discretized using Finite Element Method (FEM) to analyze the deformation and vibration of the blade. The aeroelastic response of the blade was obtained by coupling these aerodynamic and structural models using a coupled BEM-FEM program written in MATLAB. The governing FSI equations of motion are iteratively calculated at each time step, through exchanging data between the structure and fluid by using a Newmark’s implicit time integration scheme. The results obtained from this paper show that the proposed modeling can be used for a quick assessment of the wind turbine blades taking the fluid-structure interaction into account. This modeling can also be a useful tool for the analysis of airplane propeller blades.